2014
DOI: 10.2147/ppa.s70712
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukemia patients’ adherence to peroral tyrosine kinase inhibitors compared with adherence as estimated by their physicians

Abstract: PurposeTo evaluate chronic myeloid leukemia (CML) patients’ adherence to peroral tyrosine kinase inhibitors in Finland and to compare this with adherence as estimated by their physicians. Other aspects studied included how patients’ knowledge of the disease and its treatment influence adherence.Materials and methodsA total of 120 CML patients were contacted between June 2012 and September 2013 in eight secondary or tertiary care hospitals in Finland. Of these, 86 participated in the study. This covers approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 24 publications
0
45
1
Order By: Relevance
“…Unlike other studies, our sample did not a l l o w u s t o a s s o c i a t e t h i s w i t h y o u n g e r a g e , l i v i n g a l o n e a n d m a l e g e n d e r , h o w e v e r [2][3][4]6,7,10,11,14,17,19,26,[28][29][30][31][37][38][39]. While others have suggested that non-adherence may be caused by complacency and sustained disease control [4,6,[29][30][31]38], this was not the case in our participants although some speculated this might be the case in settings without public health care.…”
Section: Quality Of Life (Qol) Impact Of CMLcontrasting
confidence: 71%
See 2 more Smart Citations
“…Unlike other studies, our sample did not a l l o w u s t o a s s o c i a t e t h i s w i t h y o u n g e r a g e , l i v i n g a l o n e a n d m a l e g e n d e r , h o w e v e r [2][3][4]6,7,10,11,14,17,19,26,[28][29][30][31][37][38][39]. While others have suggested that non-adherence may be caused by complacency and sustained disease control [4,6,[29][30][31]38], this was not the case in our participants although some speculated this might be the case in settings without public health care.…”
Section: Quality Of Life (Qol) Impact Of CMLcontrasting
confidence: 71%
“…From a total of 341 identified abstracts of journal articles published within the past ten years, 67 described QoL and treatment adherence in patients with CML and were thus selected for full-text analysis -five used qualitative methods [19,29,35,37,38].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As few as 14% of CML patients were perfectly adherent in a Belgian example described by Noens et al (2009) while a third of the patients had to be classified as non-adherent. Also, in a Finnish sample only 23% of patients were highly adherent (Kekale et al 2014). Similarly, in a US sample described by Darkow et al (2007) 31% of the patients reported a treatment interruption within a year of observation.…”
Section: Introductionmentioning
confidence: 71%
“…Interestingly, Kakele et al conducted a study to compare adherence reported by patients with that perceived by their physicians 42 and found that physicians were too optimistic in assessing their patients' adherence.…”
Section: How Should We Measure Pros In CML Clinical Research?mentioning
confidence: 99%